Life Cycle Assessment of Acetylene - Zhou, Zhiming; Yu, Chaojun; Wang, Mengqin; Li, Manman; Ran, Changrong (Asian Journal of Chemistry, 2011)
Life cycle assessment is an objective method evaluating the environment pressure of industrial products, process and activities. In this paper, the life cycle assessment method was used to investigate the energy consumption and environmental burden of acetylene production with partial oxidation technology with natural gas. Through analyzed, the result shows the impact of acidification potential was 93 % in the overall impact. The life cycle impact assessment of each pollutant showed that the direct emission of naphthalene is the main sources of environmental burden and the share is 51.02 %. The impact of carbon dioxide and COD were in the second position, which shared 16.75 and 14.79 %, respectively.